Profit Theory–Where do we go from Here - Bernstein, Peter L. (Quarterly Journal of Economics, 1953)
Introduction, 407. — I. Various meanings of profit, 407. — II. Relationship of corporate management to earnings, 414. — III. Maximizing profits by minimizing taxes, 416. — IV. Maximizing aggregate profits or rate of profit, 417. — V. Windfall profits, 419. — VI. Conclusion, 420.